Heteronormativity, Masculinity and Prejudice in Mobile Apps: The Case of Grindr in a Brazilian City - Luiz Alex Silva Saraiva; Leonardo Tadeu dos Santos; Jefferson Rodrigues Pereira (BBR: Brazilian Business Review)
In this study our goal was to examine the masculinity associated to heteronormativity in a gay app from the users’ point of view, which was made through an inductive study based on semistructured interviews with app users. Main results suggest that Grindr is used as a contemporary form of sociability, mainly because it provides comfort and distance from segregated spaces. At the same time, it allows discretion in sexual encounters, which only happen between “equals”: white, young, athletic, handsome, and not effeminate men, and all those who differ from this profile are repelled. Heteronormativity imposes a pattern of masculinity that has overwhelmed everyone indiscriminately. Those who do not fit this profile can only be resigned to a secondary role at virtual community. Thus, technologies like this can aggravate marginalization of those already on the society fringes if forms of sociability continue to reproduce the oppression of prevailing heteronormativity.